The Study of APIPA Model Concept Development through the Application of Analytical Hierarchy Process (AHP) - Syahrir, Syahrir; Tjalla, Awaluddin; Triana, Dinny Devi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Improving the quality of teacher performance programs certainly requires the important role of teachers and school leaders. The role of teachers can be seen in the implementation of performance programs which require systematic and structured evaluation of performance programs. The results of the evaluation and monitoring of the implementation of the teacher performance program by school leaders are used as material for consideration in making decisions about the quality level of the teacher performance program. Making this decision is very difficult for a school leader in evaluating teacher performance programs. In this case, a modified program evaluation was developed by the CIPP model program evaluation with ALKIN model program evaluation. The research used Development Research (R&D) using 4D design (Define, Design, Development, Dissemination). The Define stage conducts a literature review regarding weaknesses in the CIPP and ALKIN model program evaluation syntax. The Design stage prepares the topology related to the main ideas of the program evaluation development syntax. The Development stage carries out operational definitions and indicators for each program evaluation syntax. The dissemination stage carries out an expert judgment or assessment of the experts who are analyzed using the analytical Hierarchical Process (AHP) to determine the consistency of the program evaluation development concept. The results using AHP are consistent with the concept of developing the APIPA model program evaluation which has the syntax Assessment, Planning, Implementation, Product, and Appreciation for evaluating teacher performance programs.